Characteristics of Children and Youth Referred for Language Assessment at Different Ages. - de Bree, Elise; Wiefferink, Karin; Gerrits, Ellen (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Early detection of language delays is essential, as language is key for academic outcomes, well-being, and societal participation. Previous studies have focused on undetected delays in young children. Much less is known about referrals at older ages. In this study, we aimed to (a) establish how many children are referred at toddler age (2-3 years) and how many at lower elementary (4-7 years), upper elementary (8-12 years), and high school (13-16 years) age; (b) evaluate characteristics of the referred children and adolescents across age groups; and (c) assess whether the ensuing classification (no language disorder [LD], developmental LD, LD + additional problems) differed across age groups. Method: We used the 2010-2014 database of the Dutch federation of speech and hearing centers, containing 18,894 cases with target ages. We established the number of referrals in each age group (Q1) and assessed the composition of the age groups in terms of speech, language, behavioral, and cognitive outcomes (Q2), as well as in terms of classification (Q3). To answer Q2 and Q3, we conducted chisquared analyses with the toddler group as reference group. Results: Late-identified LDs exist: There were new referrals in all age groups. Compared to older age groups, the toddler group contained fewer girls and multilingual children. The toddler group also contained fewer children without an LD and more children with LD + additional problems. Conclusions: Reassuringly, children with multiple language problems are referred earliest. However, late-identified LDs exist, even at high school age. Girls and multilingual children tend to be missed at younger ages. More work on awareness and identification of language delays is needed, requiring awareness, knowledge, and tools for educational professionals.